2013
DOI: 10.3168/jds.2012-5493
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the microbiota of teat apices of clinically healthy lactating dairy cows, with special emphasis on coagulase-negative staphylococci

Abstract: Swab samples (n=72) obtained from the teat apex of lactating dairy cows without visual signs of inflammation (n=18) were gathered on 2 well-managed Flemish dairy herds (herds 1 and 2) during the same month to assess the bacterial diversity of teat apices before milking. A combination of both culture-dependent [plating and (GTG)(5)-PCR fingerprinting of the colonies] and culture-independent [denaturing gradient gel electrophoresis (PCR-DGGE)] techniques indicated that the teat apices contain a wide diversity of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
55
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 44 publications
15
55
0
4
Order By: Relevance
“…These inconsistencies could indicate strain dependence of the pathogenic versus protective potential of CNS. Although CNS are abundantly present on the teat apices and in the immediate environment of cows, differences exist between species in their adaptation to different niches (De Vliegher et al, 2003;Taponen et al, 2008;Piessens et al, 2011;Braem et al, 2013;De Visscher et al, 2014). Previously, S. chromogenes, Staphylococcus epidermidis, Staphylococcus haemolyticus, Staphylococcus simulans, and Staphylococcus xylosus have been identified as the CNS species most likely to cause IMI (Piessens et al, 2011;Vanderhaeghen et al, 2014).…”
Section: Short Communicationmentioning
confidence: 97%
“…These inconsistencies could indicate strain dependence of the pathogenic versus protective potential of CNS. Although CNS are abundantly present on the teat apices and in the immediate environment of cows, differences exist between species in their adaptation to different niches (De Vliegher et al, 2003;Taponen et al, 2008;Piessens et al, 2011;Braem et al, 2013;De Visscher et al, 2014). Previously, S. chromogenes, Staphylococcus epidermidis, Staphylococcus haemolyticus, Staphylococcus simulans, and Staphylococcus xylosus have been identified as the CNS species most likely to cause IMI (Piessens et al, 2011;Vanderhaeghen et al, 2014).…”
Section: Short Communicationmentioning
confidence: 97%
“…The absence of coagulase production in transformed S. aureus remarkably diminished its intramammary virulence in mice (Jonsson et al, 1985); this most likely also relates to the minimal virulence of CNS in mice at first, as observed in the current study. The lower pathogenicity of the CNS strains compared with S. aureus explains the high prevalence of the former pathogens in the milk of clinically healthy cows and their less detrimental effects during bovine mastitis (Pate et al, 2012;Braem et al, 2013;Oikonomou et al, 2014).…”
Section: Experiments 2: Imi Of Mice With Different Cns Strainsmentioning
confidence: 99%
“…In addition, the relevance of arginase for skin-associated CNS should be further investigated, as this may have important clinical implications. Some CNS are not only important opportunistic pathogens in humans; they may also affect mastitis in dairy herds (1,6,36). It has been suggested that the arginase activity of Helicobacter pylori (46) and Bacillus anthracis (47) plays an in vivo role in host-pathogen interactions, via inhibition of host nitric oxide production and T cell proliferation (48).…”
Section: Discussionmentioning
confidence: 99%
“…Hansen, Hør-sholm, Denmark) and S. carnosus 10P1-3 and S. xylosus 10P1-1 (Danisco, Copenhagen, Denmark) were isolated from commercial meat starter cultures (35). The authenticity of all strains was confirmed at the species level through rpoB gene sequencing (36). All strains were stored at Ϫ80°C in brain heart infusion (BHI) medium (Oxoid, Basingstoke, Hampshire, United Kingdom), supplemented with 25% (vol/vol) glycerol as a cryoprotectant.…”
Section: Methodsmentioning
confidence: 99%